2013
DOI: 10.2460/javma.243.12.1719
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a point-of-care urine bacteriologic culture test in dogs

Abstract: Use of the CCSP led to accurate exclusion of UTI in dogs without a UTI but was less reliable for diagnosis of UTI, particularly infections caused by gram-positive cocci. Standard aerobic microbiological culture remains the gold standard for detection of UTI in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
1
15
2
Order By: Relevance
“…However, in former studies microscopy was interpreted by experienced technicians or diplomats at referral hospitals, and not by veterinary nurses and veterinarians under busy daily conditions. The accuracy of in‐house bacterial culture in this study was also lower than previously reported with respect to growth or no growth . At least 2 factors might cause this difference: (i) urine collection method and (ii) transportation time to the reference laboratory.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…However, in former studies microscopy was interpreted by experienced technicians or diplomats at referral hospitals, and not by veterinary nurses and veterinarians under busy daily conditions. The accuracy of in‐house bacterial culture in this study was also lower than previously reported with respect to growth or no growth . At least 2 factors might cause this difference: (i) urine collection method and (ii) transportation time to the reference laboratory.…”
Section: Discussioncontrasting
confidence: 76%
“…The accuracy of in-house bacterial culture in this study was also lower than previously reported with respect to growth or no growth. 12,13,30 At least 2 factors might cause this difference: (i) urine collection method and (ii) transportation time to the reference laboratory. Cystocentesis was the main collection method in the previous studies, in contrast to our study in which the majority of samples were collected by voluntary voiding.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians must consider whether they are using these tests to recover isolates for subsequent identification and testing by a microbiology laboratory or whether they desire (or require) identification in‐house, as would be the case for in‐house susceptibility testing. At least one of these assays offers a limited ability to determine antimicrobial drug susceptibility, but this component of the kit was found to generate inaccurate results in one field study …”
Section: What Action Should Be Taken To Reduce the Risk And Occurrencmentioning
confidence: 99%
“…For example, one expert reached an accuracy of 100% using Flexicult Vet for bacterial identification [4]. On the other hand, less experienced evaluators achieved the lower accuracies of 53% [4], 58-77% [17], and 92-98% [18]. Furthermore, the test's AST performance resulted in accuracies between 39 and 99% [4,17,18].…”
Section: Introductionmentioning
confidence: 99%